THE APPLICATION OF PROJECT-BASED LANGUAGE LEARNING IN BASIC ENGLISH EDUCATION IN MAINLAND CHINA - Xu Yong Jun; Kok Jin Kuan; Gerard Sagaya Raj a/l A Rajoo; Siah Poh Chua (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Abstract: Project-based language learning (PBLL) is a language teaching method which organizes instructional activities by doing projects. Many language teachers regard PBLL as a powerful and effective language teaching method and conduct a lot of studies to explore the application of PBLL in the different ESL/EFL learning contexts. However, PBLL needs to be adapted and localized to cater to the features of local language teachers, students and local learning context when it is brought in a particular ESL/EFL learning context. So far, fewer studies have been conducted to explore the application and the localization of PBLL in basic English education in mainland China. Therefore, this paper constructs a new model of PBLL based on the features of basic English education in mainland China and follows this model to conduct PBLL in a secondary school in Ningbo China. The experimental results reveals that the new model of PBLL can promote students’ language learning, content learning and integrated skills’ development, which manifests that the new model of PBLL is feasible and reasonable.